Sustainable Business Models for Services Using Semantic Web Components: Insights from the Field - Tate, Mary; Furtmueller, Elfi (Software Business. From Physical Products to Software Services and Solutions, 2013)
Semantic web technologies for Human Resource Information Systems (HRIS) are yet to fulfil their full potential. In this paper we reflect on an e-recruiting service development project using semantic web technologies. We use a modified Action Design Research (ADR) lens to organize insights from an innovative, entrepreneurial service offering. The results show that achieving sustainable business models for e-recruiting services based on semantic web components is non-trivial. It requires a rich and continuous interplay between theoretical knowledge (semantic web, service management, and subject-area knowledge); technical knowledge and expertise in building semantic web components; and the community of applicants and recruiters, who use and extend the sematic web components into new service offerings. We further find that the complex, interactive, adaptive, multi-disciplinary and iterative nature of HRIS projects creates challenges in communicating between the stakeholders, and in extracting and presenting theoretical contributions.